2013
DOI: 10.1007/s10552-013-0252-7
|View full text |Cite
|
Sign up to set email alerts
|

Exercise after diagnosis and metabolic syndrome among breast cancer survivors: a report from the Shanghai Breast Cancer Survival Study

Abstract: Metabolic syndrome (MetS) is an established risk factor for cardiovascular diseases and mortality. Limited data are available on the prevalence of MetS and its association with exercise among breast cancer survivors. The present study included 1696 breast cancer survivors from the Shanghai Breast Cancer Survival Study, a population-based prospective cohort study conducted between April 2002 and October 2011 in Shanghai, China. All women had a physical examination taken at study clinic approximately 60 months p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
5
14
0
2
Order By: Relevance
“…Holmes et al demonstrated a reduction in the risk of death due to breast cancer in women who exercised (3-5 hours per week) after treatment compared to women with a sedentary lifestyle (18). Other research groups have confirmed these results (19)(20)(21)(22). Walsh et al and Daroux-Cole et al suggested that exercise stimulated the immune system in cancer patients (23,24).…”
mentioning
confidence: 77%
“…Holmes et al demonstrated a reduction in the risk of death due to breast cancer in women who exercised (3-5 hours per week) after treatment compared to women with a sedentary lifestyle (18). Other research groups have confirmed these results (19)(20)(21)(22). Walsh et al and Daroux-Cole et al suggested that exercise stimulated the immune system in cancer patients (23,24).…”
mentioning
confidence: 77%
“…However, our results suggest that the metabolic abnormalities and depression observed in BCS may not be attributable to low cardiorespiratory fitness, as these risk factors were present even though a higher VO 2 max was observed in BCS than non-cancer controls. Despite this finding, many studies suggest that depressive symptoms and metabolic dysfunction improve with exercise in BCS [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of data have shown that metabolic syndrome (MetS) and its independent components are related with plethora of cancers, including a higher risk of having breast cancer (Esposito et al 2012;Uzunlulu, Telci Caklili, and Oguz 2016;Park et al 2017). Similarly, breast cancer survivors were also reported to be susceptible to MetS (Bhandari et al 2014;Bao et al 2013).…”
Section: Introductionmentioning
confidence: 99%